2020
DOI: 10.1016/j.isci.2020.101115
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Algal Photosynthetic Photon Efficiency by Pulsed Light

Abstract: We present experimental results demonstrating that, relative to continuous illumination, an increase of a factor of 3-10 in the photon efficiency of algal photosynthesis is attainable via the judicious application of pulsed light for light intensities of practical interest (e.g., average-to-peak solar irradiance). We also propose a simple model that can account for all the measurements. The model (1) reflects the essential rate-limiting elements in bioproductivity, (2) incorporates the impact of photon arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
6
32
0
Order By: Relevance
“…For a batch cultivation system, Qiang et al (1998 ) found an increase in biomass productivity from 200 to 7.5 mm; however, we experimentally verified that the behavior of batch and continuous systems at ultra-thin light paths is considerably different. Experimental results and previous considerations show that an indefinite decrease in the reactor thickness cannot lead to an increase in cultivating performances in continuous systems and suggest the existence of an optimal light path value (as conceptualized in other studies ( Richmond et al, 2003 ; Zarmi et al, 2020 ).…”
Section: Resultssupporting
confidence: 63%
“…For a batch cultivation system, Qiang et al (1998 ) found an increase in biomass productivity from 200 to 7.5 mm; however, we experimentally verified that the behavior of batch and continuous systems at ultra-thin light paths is considerably different. Experimental results and previous considerations show that an indefinite decrease in the reactor thickness cannot lead to an increase in cultivating performances in continuous systems and suggest the existence of an optimal light path value (as conceptualized in other studies ( Richmond et al, 2003 ; Zarmi et al, 2020 ).…”
Section: Resultssupporting
confidence: 63%
“…When discussing the regulatory effect of light on the growth of microalgae, as a rule, not the entire light flux is studied, but that part of it that has the greatest physiological activity. This radiation corresponds to the visible part of the spectrum in the wavelength range 400-700 nm and is called photosynthetically active radiation [46]. When characterizing the light conditions for microalgae growth, the light intensity, duration of lighting and the spectral composition of the light flux are taken into account.…”
Section: Light As An Environmental Factor Of Microalgae Growthmentioning
confidence: 99%
“…The duration of lighting is also of great importance, both from the point of view of ensuring maximum microalgae productivity, and for minimizing energy costs during cultivation. The practice of using continuous lighting or alternating light and dark cultivation cycles is known, including pulsed (blinking) lighting, which is characterized by a rapid change in light and dark periods [46,53,54]. The use of light and dark cultivation cycles is associated with the peculiarities of photosynthesis-a complex multistep process in which light-dependent photochemical reactions and dark reactions are distinguished, wherein the dark reaction of photosynthesis is not dependent on the presence of light [14].…”
Section: Light As An Environmental Factor Of Microalgae Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The author also explained how the photonic efficiency enhancement depends on the optical pulse and the photon flux density of time scales. More specifically, the key is through the correct timing of the algae cell light/dark cycle to avoid photosynthetic pathway jams [40]. The results from the previous literature explain the relationship between leaf photosynthesis and the L/D cycle in the light pulse process by considering the PIs pool.…”
Section: Discussionmentioning
confidence: 99%